(3eQUGO GdeQGO aj TQM JNejS HGfJ SYGOs - (3GdcdjSj, GdYQjGfj, YKeGf Hf YHO Gddg, J(B1168(3g`s ((3ehSi Hf YHO GdHGbj Hf Ydj GdeQJVi Hf eUWai GdHhRbQis)
(3ChdgG (B:s
(3GdMeO ddg Pj GdYah hGdZaQGfhHYO aEf GdbUjOI GdTgjQI HHGfJ SYGOef efXheGJ cYH Hf RgjQde cGfJ ef CTQa GdbUGFO aj eOM CaVd GdQSds
(3BNQgG (B:s
(3hNJe HPcQ GdehJ hGdafGA Ydi hUa GdTgGOI GdehLHI ddbGA aj OGQ GdHbGA hdG GQJjGH aj Cfg dG aQb Hjf GdehJ hGdaQGb YfO CQHGH GdGTJjGb GfJgis
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B1157(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 209s
(3eYLe GdeDdajf(B: 2 / 363s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs